A 'smart' aptamer-functionalized continuous label-free cell catch–transport–release system. Issue 35 (22nd July 2021) - Zhang, Bozhen; Wang, Canran; Du, Yingjie; Paxton, Rebecca; He, Ximin
Abstract : A 'smart' aptamer-functionalized catch–transport–release system was developed with facile fabrication for continuous, selective, high-throughput label-free cell sorting. Abstract : Label-free cell sorting devices are of great significance for biomedical research and clinical therapeutics. However, current platforms for label-free cell sorting cannot achieve continuity and selectivity simultaneously, resulting in complex steps and limited reliability. Here, an immunoaffinity-based cell catch–transport–release thermo-chemo-mechanical coupling hydrogel (iCatch) device is reported. It contains a temperature-responsive hydrogel that can generate spatial movement synergically with the reversible binding of affinity handle modified. The functionalized hydrogel is embedded inside a biphasic microfluidic platform to enable cell transportation between the flows. The cell sorting capability and biocompatibility of the iCatch device were validated with CCRF-CEM cells as a proof-of-concept, and CCRF-CEM-specific aptamers with thermo-responsive affinity as well as a hydrogel with temperature-dependent volume were employed accordingly. A cell catching efficiency of ∼40% and a recovery rate of ∼70% were achieved. The iCatch device provides a high-throughput (∼900 cells mm −1 s −1 ) platform for cell sorting and is ultimately valuable for downstream biomedical applications.